The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1038/s41417-019-0140-8
|View full text |Cite
|
Sign up to set email alerts
|

CLEC5A expressed on myeloid cells as a M2 biomarker relates to immunosuppression and decreased survival in patients with glioma

Abstract: Glioma is the most common tumor in the central nervous system that portends a poor prognosis. Key genes negatively related to survival may provide targets for therapy to improve the outcome of glioma. Here, we report a protein-coding gene CLEC5A, which is the top 1 gene by univariate Cox regression analysis of 524 primary GBM samples. Expression of CLEC5A is significantly correlated with decreased overall survival in patients with glioma via large-scale analysis. An analysis of 2589 patient samples showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…Co-culture assay showed that OC cells overexpressing CLEC5A could enhance the M2 polarization of M2 macrophages ( Figure 6D and Supplementary Figure 4C ). Moreover, overexpression of CLEC5A in M2 macrophages can also enhance its own M2 polarization ( Figure 6E ), as in a previous study ( Tong et al, 2020 ). The correlation analysis between CLEC5A and immune checkpoint gene suggested that CLEC5A was positively correlated with CD80, CD86, PD-L1, CTLA4, CD47, and PD-L2 ( Figure 6C ).…”
Section: Resultssupporting
confidence: 87%
“…Co-culture assay showed that OC cells overexpressing CLEC5A could enhance the M2 polarization of M2 macrophages ( Figure 6D and Supplementary Figure 4C ). Moreover, overexpression of CLEC5A in M2 macrophages can also enhance its own M2 polarization ( Figure 6E ), as in a previous study ( Tong et al, 2020 ). The correlation analysis between CLEC5A and immune checkpoint gene suggested that CLEC5A was positively correlated with CD80, CD86, PD-L1, CTLA4, CD47, and PD-L2 ( Figure 6C ).…”
Section: Resultssupporting
confidence: 87%
“…However, it had no significant effect on the expression of other M1 macrophage markers, such as CD68 [ 21 ], TLR2 / TLR4 [ 46 ], which are highly expressed in THP1 cells (Supplementary Figure S5), and human leukocyte antigen-DR alpha ( HLA-DRα ) [ 18 , 21 ] ( Figure 4(a,b) ). In contrast, the majority of M2-related genes, including CD209 [ 47 ], C-type lectin domain family 5-member A ( CLEC5A ) [ 48 ], CD200 R [ 49 ], sphingosine kinase 1 ( SPHK1 ), class A scavenger receptor 1 ( SRA1 ) [ 50 ], IL1 receptor, type II ( IL1R2 ) [ 49 ], and CD163 [ 51 ], were significantly increased in LEV-treated, compared to vehicle-treated, cells ( Figure 4(a,c) ). The functional activity of LEVs in regulating the expression of macrophage-polarized genes was further verified using density-purified LEVs, which did not significantly increase the expression of M1-related genes (CD68, TLR2, HLA-DRα ), however did increase M2-related genes ( CLEC5A, SRA, CD163 ), and was specific when considering the effects driven by medium concentrates (Supplementary Figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…For example, CLEC5A is a member of the C‐type lectin/C‐type lectin‐like domain (CTL/CTLD) superfamily and is reported to be an M2 biomarker, associated with immunosuppression. CLEC5A overexpression decreases survival time in glioma patients 29 . CHI3L1 encodes a glycoprotein member of the glycosyl hydrolase 18 family that is an immunomodulatory molecule, which may inhibit the PI3K/AKT pathway in GBM.…”
Section: Discussionmentioning
confidence: 99%